Development Of Local Economic Independence Through Optimizing Of Village Fund Management - Zulkarnaini Zulkarnaini; Dadang Mashur (Iapa Proceedings Conference, 2018)
Currently villages in Indonesia are required to be able to give birth to quality economic growth and sustainable. Quality economic growth is a concept of strengthening and contribution contributed by the real economy sector in the village. Therefore, the development and empowerment of rural communities through the management of the Village Fund or Village Fund Allocation Fund must be balanced. Because to empower the potential of the village optimally and sustainably, funding for the village needs to be focused not only to build village, but more empowered to become a self-constructing village. This study aims to develop local economic independence through optimizing the management of Village Funds in Siak Subdistrict Siak District and any factors that influence the development of local economic independence. This research is a descriptive qualitative research with sampling technique used is snowball sampling. The research informant is the apparatus involved in the implementation of the Village Fund program and the community leaders who know the program. Data collection was done by interview and observation technique, after the data collected and then analyzed by using qualitative descriptive analysis. The results of research indicate that the development of village economy can be done by strengthening the performance of local economic institutions such as BUMDes through various aspects. To achieve this, an integrated movement between the community, BUMDes and the government is realized in the form of partnership. Activities that can be done is to optimize the function of central and local entrepreneurial institutions to support various efforts to inventory the potential of local economic resources. With the development of household industry activities, it will facilitate efforts to establish cooperation between local economic development institutions that exist and thus create a process of sustainable community empowerment of villages.